The role of service marketing mix on the decision to choose a school: an empirical study on elementary schools - Syarif Iskandar; Burhan Rifuddin; Dodi Ilham; Rahmat Rahmat (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
This study aims to analyze the effect of the service marketing mix, including Product, Price, Place, Promotion, People, Process, and Physical Evidence, on parents’ decision-making in choosing elementary schools. This type of research is descriptive analysis. The research sample is parents or guardians of elementary school students totaling 321 people in Palopo; the sampling technique used is a simple random sampling method. The data collection technique used was an online questionnaire via Google Form. The data analysis method used is Structural Equation Modeling (SEM) analysis with data processing tools using SmartPLS 3.0 software. The results of data analysis show that: Product, Price, Place, Promotion, People, Process, and Physical Evidence have a positive and significant effect on the decision to choose an elementary school in Palopo. The novelty of this research is the relationship model of the service marketing mix to the decision to choose an elementary school.